Synthesis, Characterization, Antimicrobial and Anticancer Studies of Metal Complexes of 2-methoxy-4-((3-methylpyridin-2-ylimino)methyl)phenol - Mishra, Akanksha; Tahlan, Sumit; Ramasamy, Kalavathy; Lim, Siong M.; Shah, Syed A. A.; Narasimhan, Balasubramanian (Mini Reviews in Medicinal Chemistry, 2020)
Background: Being derived from primary amine and aromatic aldehyde, Schiff base and their complexes have an imperative role in the improvement of inorganic chemistry, which are broadly studied as coordination compounds and are gradually becoming more important in biochemical and analytical applications. Methods: They have also been used for antibacterial, antifungal, anticancer, antitubercular activities. Novel synthesised Schiff’s base 2-methoxy-4-((3-methylpyridin-2-ylimino)methyl)phenol (SB) and its metal complexes (Zn[II], Cu[II], Co[II] and Ni[II]) were characterised by UV, IR and NMR spectroscopy. Formation of the Schiff base and the metal (Zn[II], Cu[II], Co[II] and Ni[II]) chelates was supported by spectral and analytical data. The ligand and metal complexes have been screened for their antibacterial activity against Staphylococcus aureus, Salmonella typhi, Escherichia coli, Klebsiella pneumoniae and antifungal activity against the fungi Candida albicans and Aspergillus niger. Further, the synthesised compounds were also screened for antiproliferative activity against the human colorectal carcinoma (HCT116) cell line using the Sulforhodamine B assay. Result: Metal complexes formed were found to enhance the potency of the Schiff base due to coordination with a copper complex, showing better activity than others. Conclusion: Copper complex was observed to be more potent than other complexes against all the pathogenic microbes and cancer cell line (HCT116).
Keywords: antimicrobial activity